Varahavtar panel in Cave 5 at Udayagiri - Temples of India Project Team (Jio Institute, 2024)
Cave 5, in particular, features a complex iconographic program aimed at legitimizing the royal patron as the conduit between humanity and the divine, represented by Vishnu in his boar form, while the cosmic waters threatening the human world fill the ground. Image courtesy: Wikimedia Commons